633 What is the Effectiveness of Dimethylglycine in Treating Autistic Symptoms in Children: a Systematic Review. (October 2012) - Haroon, M; Ryan, G; Randell, M; Wilson, J; Khatau, T
Abstract : Background and Aims: Dimethylglycine, an amino-acid derivative, has been proposed as a treatment for Autism. A systematic review was conducted to synthesize the best evidence relating to this topic. Methods: The study was conducted by members of CHARGE (Child Health Applied Research Group: East-midlands) using a methodology informed by The PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analysis). A clinical question using a standard PICO (Patient, Intervention, Comparison, Outcome) format was used to inform the search terms and search strategy. The search was executed on Medline, Embase, The Cochrane Library, two meta-search engines and ISI-Web of Science. In addition, a search of the grey literature was conducted. Retrieved studies were independently appraised by two reviewers for relevance and quality using the Cochrane Collaboration's tool for assessing risk of bias. Data was extracted onto a standardised proforma. Results: Only one small clinical trial (n=39) could be included in our final analysis and this showed statistically non-significant effects for parentally reported improved behaviour (58% [drug] vs. 53% [placebo]). There was no difference between the two groups for adverse outcomes. This trial and two excluded trials highlighted the critical importance of proper methodology for conducting future trials in autism. These include the need for appropriate: power, outcomes and follow-up, and due consideration of the clinical spectrum of autistic patients involved in the trials. Conclusion: There is insufficient evidence to support the use of dimethylglycine for the treatment of children with autism. Further robust research is required on this topic.